Coefficient Analysis of Shell and Tube Type Heat Exchangers - Hafizh, Firmansyah; Suares, Reza Mardiansah; Ikhsanudin, Zaky; Safitri, Puspa Dinda; Ghozali, Achmad Imam; DwiYanto, Agus; Firmansah, Achmad Robi; Rujianto, Andi Azrial Akbar; Saputro, Wiliandi; Issafira, Radissa Dzaky (BIOMEJ, 2024)
Heat exchanger is a device used to transfer heat between two fluid systems at different temperatures. In this research, the heat exchanger used is in the form of a shell and tube which studies the mechanism of heat transfer between hot water and cold water both in contra flow. The purpose of this research is to analyze the relationship of heat transfer coefficient with changes in flow regime in shell and tube contra flow heat exchanger. This research was carried out by measuring the inlet and outlet water temperatures for the counter flow configuration, then analyzing the effectiveness calculation using the LMTD method. As a result, the inlet and outlet water temperature values for the counter flow configuration are obtained, then the effectiveness of the heat exchanger is assessed using the LMTD formula where the effectiveness of the heat exchanger for counter flow. The purpose of the research is to understand the heat exchanger system and analyze the performance of the shell and tube heat exchanger.